The United Kingdom and Ireland association of forensic toxicologists forensic toxicology laboratory guidelines (2018). Issue 5 (September 2018) - Elliott, Simon P.; Stephen, Duncan W.S.; Paterson, Sue
Abstract: In 2010, the United Kingdom and Ireland Association of Forensic Toxicologists (UKIAFT) created forensic toxicology laboratory guidelines. This represents a revision of those guidelines as a result of the changing toxicological and technical landscape.